Analysis of rebounded balls in a team handball match - Burger, A.; Rogulj, N.; Foretic, N.; Cavala, M. (SportLogia, 2013)
We have analysed fifteen matches played by the male Croatian national handball team at the World Championship in Tunisia in 2005 and those played at the European Championship in Austria in 2010. The research has been conducted with the purpose of establishing the frequency of shooting from certain zones, i.e. from the attacking positions, the frequency of rebounded balls off the goal keeper or off the goal frame, as well as establishing where or who to the performed shots rebound. The field for the position game was divided into five zones: the left wing player, the left back player, the middle back player, the right back player and the right wing player. The mentioned zones also represent the rebounding zones. The results have shown that most shots were performed from the central zone, while the frequency of shooting from other zones was mostly equally disposed. The average number of the balls rebounded off the goal keeper or the goal frame is 17.6 balls. In 71% of the cases, the rebounded balls end in the possession of defence players which is the consequence of their close position in relation to the ball. The biggest number of rebounded balls (40%) returns to the central zone. By the X2 test we established that the largest number of shots performed from a certain zone rebounds in the same zone, or, in rare cases, in the nearby zone. This greatly depends on the shooting angle, which is mostly in a straight line in relation to the goal, and on the goal keeper`s position in relation to the ball. The research implies the need for practising this game segment during handball training by the means of specific and situation training exercises.